2012
DOI: 10.1007/s00405-012-2221-2
|View full text |Cite|
|
Sign up to set email alerts
|

Experience of 11 years use of cidofovir in recurrent respiratory papillomatosis

Abstract: Recurrent respiratory papillomatosis (RRP) is a viral induced disease, associated with exophytic epithelial lesions affecting the upper airways. Problem of treatment is the high recurrence of papilloma growth after surgical removal; therefore adjuvant therapy schemes have been established. Cidofovir was one of the agents used off-label in adjuvant therapy in the last years. However, there is ongoing discussion about the effectiveness and possible side effects. Aim of our study was to share our experience in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
0
16
0
3
Order By: Relevance
“…CDV represents an option to reduce the risks of frequent surgical debulking and airway obstruction in children and adults with recurrent or severe disease (Derkay et al, 2013). CDV is nowadays recognized as an adjuvant therapy for the management of this disease (Tjon Pian Gi et al, 2013;Graupp et al, 2013). A type specific real-time PCR to measure HPV6 and HPV11 DNA loads in patients with recurrent respiratory papillomatosis treated with CDV, indicated that the drug significantly reduced viral load following intralesional application (Mikolajczak et al, 2012).…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-papillmentioning
confidence: 98%
“…CDV represents an option to reduce the risks of frequent surgical debulking and airway obstruction in children and adults with recurrent or severe disease (Derkay et al, 2013). CDV is nowadays recognized as an adjuvant therapy for the management of this disease (Tjon Pian Gi et al, 2013;Graupp et al, 2013). A type specific real-time PCR to measure HPV6 and HPV11 DNA loads in patients with recurrent respiratory papillomatosis treated with CDV, indicated that the drug significantly reduced viral load following intralesional application (Mikolajczak et al, 2012).…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-papillmentioning
confidence: 98%
“…While uncontrolled and retrospective studies have shown intralesional cidofovir to be effective for RRP with approximately 40-50% of patients achieving remission, a systematic review on adjuvant antiviral therapy for the treatment of RRP identified only one randomized double-blind, placebo-controlled trial of intralesional cidofovir administered at the time of surgical debulking with significant clinical improvements in both the cidofovir and placebo groups and no significant difference between the two groups. [76][77][78][79][80] Bevacizumab is a recombinant humanized monoclonal antibody that blocks angiogenesis by binding to and inhibiting the biological activity of human vascular endothelial growth factor A (VEGF-A). 81 Intralesional bevacizumab has been shown to prolong the intersurgical interval in small case series, 81 while systemic bevacizumab has been shown to be of benefit in patients with highly aggressive disease and those with pulmonary involvement.…”
Section: Disease Coursementioning
confidence: 99%
“…De esta manera, quedaron 22 artículos relacionados específicamente con el uso de cidofovir en papilomatosis respiratoria recurrente juvenil, enfocados a la recurrencia de la enfermedad. Este grupo de estudios incluyó un ensayo clínico aleatorizado, 17 18 series de casos, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] un estudio de casos y controles 36 y dos reportes de casos.…”
Section: Resultsunclassified